Effect of service quality, price fairness, justice with service recovery and relational bonds on customer loyalty: Mediating role of customer satisfaction - Rana Muhammad Shahid Yaqub; Fairol Halim; Arfan Shehzad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Customer loyalty has gained foremost attention among the practitioners and the academic researchers because of its proximity to organizational growth, profit and survival. Based on existing literature, this study has highlighted a few critical issues related to the telecommunication sector in Pakistan such as the decline in subscriber growth, decrease in average revenue, and the increasing trend of users switching among the telecom operators. The objective of the present study is to analyze the impact of perceived service quality, price fairness; justice to service and relational bonds on customer loyalty with the mediating role of customer satisfaction .the framework of the present study is based on the expectancy confirmation model and the principles of reciprocity. Data for the current study was collected from 539 prepaid subscribers based in four major capital cities of Pakistan through questionnaires by adopting the proportionate stratified random sampling. The collected data was analyzed by using SPSS version 23 and the Smart PLS Structure Equation Modeling (PLS-SEM). Findings of the study revealed that perceived service quality and customer satisfaction are the main driving forces to customer loyalty. Moreover, customer satisfaction successfully mediates between exogenous and endogenous variables. The present study has also suggested some theoretical and practical contributions.
Keywords: 330; price fairness; Justice with service recovery; relational bonds; telecom sector